2010
DOI: 10.1007/s00330-010-1897-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion imaging using adenosine-induced stress dual-energy computed tomography of the heart: comparison with cardiac magnetic resonance imaging and conventional coronary angiography

Abstract: Adenosine stress DECT can identify stress-induced myocardial PD in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
96
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 29 publications
0
96
1
5
Order By: Relevance
“…Dual-energy CT technology may provide image acquisition using more than a single energy X-ray spectrum (30,31). Dual-energy CT represents a promising technique for the integrative analysis of coronary artery morphology and myocardial blood supply; furthermore Dual-energy CT is in good agreement with invasive coronary angiography and SPECT (30).…”
Section: Ct Technical Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-energy CT technology may provide image acquisition using more than a single energy X-ray spectrum (30,31). Dual-energy CT represents a promising technique for the integrative analysis of coronary artery morphology and myocardial blood supply; furthermore Dual-energy CT is in good agreement with invasive coronary angiography and SPECT (30).…”
Section: Ct Technical Notesmentioning
confidence: 99%
“…It is well known that stress perfusion abnormalities occur before wall motion dysfunction (50). Therefore, additional scans acquired during pharmacologic stress with adenosine or dipyridamole may detect reversible perfusion defects of myocardium (31,(51)(52)(53). Therefore, the stress-CCT may be indicated: in symptomatic patients at intermediate risk of …”
Section: Ct Technical Notesmentioning
confidence: 99%
“…Based on the specific absorption characteristics of iodine for different X-ray energies, DECT allows mapping of intra-myocardial iodine extent and distribution, and small sample studies have demonstrated the feasibility of this technique to detect myocardial perfusion deficits [15][16][17]. However, large-scale studies examining stress DECT-MPI are lacking [18,19]. Furthermore, the diagnostic performance of combined CCTA and stress DECT-MPI compared with CCTA, based on a combined anatomicalphysiological reference standard, has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a paper was published in European Radiology by Ko et al [15], which compared adenosine stress perfusion dual-energy CT and CTA of the coronary arteries with stress-perfusion MRI and conventional coronary angiography; they showed that adenosine-stress dualenergy-CT can identify perfusion defects with a sensitivity, specificity and accuracy of 89%, 78%, and 82%, respectively. But, at the moment, the radiation dose from such combined protocols is still too high to use in the daily clinical routine.…”
mentioning
confidence: 99%
“…Adenosine stress-perfusion imaging [11][12][13][14][15] is feasible and several studies show promising results. The clear advantage of CT in this setting is the complementary evaluation of coronary artery anatomy and myocardial function, which overcomes current shortcomings of CTA.…”
mentioning
confidence: 99%